The Economic Evaluation of Rare Disease Medicines - Skarayadi, Oskar; Untari, Eka Kartika; Octaviani, Peppy; Larasati, Niken (Jurnal Kesehatan Masyarakat, 2024)
Economic evaluation of rare diseases and orphan drugs has gained prominence among scientists, managers, and the general public. This challenging problem requires evaluation and analysis from a variety of perspectives. Economic assessment of technologies can support decision-making and resource allocation. The research objective describes and discusses several important issues when addressing economic evaluation in rare diseases and orphan drugs. The method used in this article review is to search the Pubmed, Scopus, and ScienceDirect databases using specific keywords for research articles published in English between 2016 and 2021. We found 537 studies that economically evaluated the cost of treating rare diseases. The selected studies met the eligibility criteria that had been established. To assess the quality of the selected papers, we used a 10-point checklist derived from Drummond's criteria for economic evaluation. Seven papers were reviewed from the initial 20 articles that met the eligibility criteria, and 537 records were initially found across the three databases. The quality of the selected papers ranged from 70% to 100% in meeting Drummond's 10-point checklist. The conclusion of this research is to consistently and continuously identify cost-effective and cost-saving solutions that may help achieve good clinical outcomes and reduce the burden of disease. Future research should focus on the clinical implementation of interventions along with accompanying economic evaluations.